2020
DOI: 10.1016/j.envpol.2020.115387
|View full text |Cite
|
Sign up to set email alerts
|

Emerging polar pollutants in groundwater: Potential impact of urban stormwater infiltration practices

Abstract: Capsule: The fate of 16 polar and semi-polar pesticides and pharmaceuticals in groundwater upstream and downstream of stormwater infiltration systems (SIS) was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Some PPPs reached very high concentration levels. The most extreme case was fluopyram, which high concentrations corroborate earlier findings from the study area (Spycher et al, 2018) but are way beyond what has been reported in the limited literature reporting fluopyram concentrations (Sjerps et al, 2019;Pinasseau et al, 2020). What the grab sampling though clearly demonstrated was the occurrence of fluopyram in the entire length of the open stream and in several tile drains.…”
Section: Surface Watersupporting
confidence: 85%
“…Some PPPs reached very high concentration levels. The most extreme case was fluopyram, which high concentrations corroborate earlier findings from the study area (Spycher et al, 2018) but are way beyond what has been reported in the limited literature reporting fluopyram concentrations (Sjerps et al, 2019;Pinasseau et al, 2020). What the grab sampling though clearly demonstrated was the occurrence of fluopyram in the entire length of the open stream and in several tile drains.…”
Section: Surface Watersupporting
confidence: 85%
“…Global climate change and increased urbanization are expected to heighten the threat of stormwater runoff contamination because of increases in the intensity of storm events and growth of urban impervious surface area. , Stormwater runoff is also a concern at military and industrial facilities because of the potential transport of contaminants off-site and recontamination of sediments following remediation efforts . The potential to augment drinking water supplies with urban stormwater runoff through managed aquifer recharge has also received increased attention in arid regions, though this recharge is dependent on improving water quality to avoid introducing contaminants into drinking water aquifers . Effective and efficient treatment of stormwater runoff entering receiving waters and underground aquifers is therefore necessary for both protection of human and aquatic health and augmentation of urban water supplies.…”
Section: Introductionmentioning
confidence: 99%
“…Cfb. In this climatology, the retention of contaminants [140,141] such as hydrocarbons [142] and heavy metals [143] or bacterial contamination [144] has also been proven, although not all contaminants behave in the same way; some are not retained in high concentrations [145,146], and components such as carbendazim, diuron, fluopyram, imidacloprid, and lamotrigine reach the groundwater [147]. The use of vegetation such as Phalaris arundinacea and Typha latifolia can absorb or modify the mobility of heavy metals [148].…”
Section: Regulation Services: Biodiversitymentioning
confidence: 97%